Determinants of corporate cash policy: Insights from private firms - Gao, Huasheng; Harford, Jarrad; Li, Kai (Journal of Financial Economics, 2013)
We provide one of the first large sample comparisons of cash policies in public and private U.S. firms. We first show that despite higher financing frictions, private firms hold, on average, about half as much cash as public firms do. By examining the drivers of cash policies for each group, we are able to attribute the difference to the much higher agency costs in public firms. By combining evidence from across public and private firms as well as within public firms across different qualities of governance, we are able to reconcile existing mixed evidence on the effects of agency problems on cash policies. Specifically, agency problems affect not only the target level of cash, but also how managers react to cash in excess of the target.